An individual-based model for sablefish: Exploring the connectivity between potential spawning and nursery grounds in the Gulf of Alaska. (July 2019) - Gibson, G.A.; Stockhausen, W.T.; Coyle, K.O.; Hinckley, S.; Parada, C.; Hermann, A.J.; Doyle, M.; Ladd, C.
Abstract: Little is known about the mechanism of transport that enables age-0 sablefish ( Anoplopoma fimbria ) to reach suitable nursery sites from spawning locations far offshore, or the strength of the connection between individual spawning sites and nursery areas, or how variability in the strength of these connections may impact recruitment success. Using a model for the early life stages of sablefish, we explored the variability in connectivity between spawning and recruitment sites that can arise solely from interannual variability in environmental forcing and its impact on transport. Our major findings are that 1) the model indicates young sablefish settling in nursery areas in the Gulf of Alaska were most likely spawned in the eastern Gulf; 2) sablefish spawned in the western Gulf of Alaska are unlikely to settle anywhere in the Gulf, and are more likely to be advected farther west, perhaps to settle in the Aleutian islands or Bering Sea (to contribute to the Alaska population, they would have to undergo an active return migration as they mature); 3) total connectivity between all spawning sites and nursery areas showed stronger correlation with recruitment estimates than the strength of connections to or from specific regions; and 4) transport to St. John Baptist Bay, a known sablefish nursery area, was not the most probable end point for sablefish spawned throughout our Gulf of Alaska model domain. This suggests that young individuals arrive at this persistent nursery area due to directional swimming behavior, highly localized spawning, or small-scale currents not captured in the hydrographic model. The fact that no single correlate in our analysis had a very strong relationship to sablefish recruitment indicates that recruitment variability arises from complex interactions between the environment and the individual, and a possible disconnect in spatial scales between the Gulf of Alaska sablefish IBM and the broader sablefish stock assessment, which includes both the GOA and the Eastern Bering Sea, as well as possible contributions from Canadian stocks to the south. Our analyses determined that although the timing and extent of this transport shows significant interannual variability, both the location of likely sablefish spawning (source) areas and the comparative strength of connectivity between spawning and nursery sites appear to be relatively consistent year-to-year.